2009
DOI: 10.1002/cssc.200800241
|View full text |Cite
|
Sign up to set email alerts
|

Novel Polymeric Materials from Vegetable Oils and Vinyl Monomers: Preparation, Properties, and Applications

Abstract: Veggie-based products: Vegetable-oil-based polymeric materials, prepared by free radical, cationic, and olefin metathesis polymerizations, range from soft rubbers to ductile or rigid plastics, and to high-performance biocomposites and nanocomposites. They display a wide range of thermophysical and mechanical properties and may find promising applications as alternatives to petroleum-based polymers.Vegetable oils are considered to be among the most promising renewable raw materials for polymers, because of thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
213
0
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 301 publications
(222 citation statements)
references
References 106 publications
0
213
0
9
Order By: Relevance
“…For example, natural oils provide an attractive alternative to current synthetic polymers based exclusively on petroleum feedstocks [5][6][7][8][9][10] . Some of the more promising polymeric substances are those obtained from fatty acids, which are biocompatible, cost effective, and biodegradable [5][6][7][8][9][10][11][12] . The specific usefulness of fatty acids is determined by the presence of carbon-carbon double bonds and acid functions, susceptible to cationic, radical polymerizations or polyesterification reactions [13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…For example, natural oils provide an attractive alternative to current synthetic polymers based exclusively on petroleum feedstocks [5][6][7][8][9][10] . Some of the more promising polymeric substances are those obtained from fatty acids, which are biocompatible, cost effective, and biodegradable [5][6][7][8][9][10][11][12] . The specific usefulness of fatty acids is determined by the presence of carbon-carbon double bonds and acid functions, susceptible to cationic, radical polymerizations or polyesterification reactions [13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…The degradation of the world polity and regional wars are not left out, because their underlying reasons and interest are centered on this limited and non-ecofriendly based material (petroleum) [1][2][3] . Sustainable resource materials like cellulose and starch, proteins, natural rubber and vegetable seed oils are capable of providing eco-friendly chemicals and polymeric based feeds as substitute to petroleum feed stocks 4 . The development of polymeric based materials (polyols and urethanes) from sustainable resources to useful industrial products cannot be overemphasized, studies has shown that medical devices, adhesives, footwear, elastomers, wall foam insulation, bone regeneration, biodiesel, lubricants, automotive interiors and their coats can be synthesized vegetable seed oils [4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…Sustainable resource materials like cellulose and starch, proteins, natural rubber and vegetable seed oils are capable of providing eco-friendly chemicals and polymeric based feeds as substitute to petroleum feed stocks 4 . The development of polymeric based materials (polyols and urethanes) from sustainable resources to useful industrial products cannot be overemphasized, studies has shown that medical devices, adhesives, footwear, elastomers, wall foam insulation, bone regeneration, biodiesel, lubricants, automotive interiors and their coats can be synthesized vegetable seed oils [4][5][6][7] . Vegetable seed oils of castor, linseed, nahar, soybean, Annona squamosal, Pongamia glabra and others have been used in the synthesis of polyesteramides 1 , polyetheramides 8 , alkyds, epoxides 9 , polyurethanes 10 and other polymeric resins.…”
Section: Introductionmentioning
confidence: 99%
“…These global issues can be subdued by the use of resource materials that are eco-friendly and renewable such as seed oils, polysaccharides (basically cellulose and starch), proteins, natural rubber, wood, and others as sustainable substitute for petroleum based feed stocks, which have finite reserves. [1][2][3] Amidst these renewable materials aforementioned, seed oils are most widely used as base materials for polymer and chemical industries due to their low toxicity, low price, ready availability and biodegradability. 2,4 Seed oils comprising of different fatty acids compositions are obtained from plants such as soybean, yellow oleanda, Pogamia glabra, sunflower, linseed, tung oil, safflower, castor etc.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Amidst these renewable materials aforementioned, seed oils are most widely used as base materials for polymer and chemical industries due to their low toxicity, low price, ready availability and biodegradability. 2,4 Seed oils comprising of different fatty acids compositions are obtained from plants such as soybean, yellow oleanda, Pogamia glabra, sunflower, linseed, tung oil, safflower, castor etc. The fatty acids profile of castor oil differs extensively from that of other plant seed oils.…”
Section: Introductionmentioning
confidence: 99%